X-Linked Inhibitor of Apoptosis Protein – A Critical Death Resistance Regulator and Therapeutic Target for Personalized Cancer Therapy - Obexer, Petra; Ausserlechner, Michael J. (Frontiers in Oncology, 2014)
Defects in apoptosis regulation are one main cause of cancer development and may result from overexpression of anti-apoptotic proteins such as Inhibitor of Apoptosis Proteins (IAPs). IAPs are cell death regulators that, among other functions, bind caspases and interfere with apoptotic signaling via death receptors or intrinsic cell death pathways. All IAPs share one to three common structures, the so called baculovirus-IAP-repeat (BIR)-domains that allow them to bind caspases and other proteins. X-linked inhibitor of apoptosis protein (XIAP) is the most potent and best-defined anti-apoptotic IAP-family member that directly neutralizes caspase-9 via its BIR3 domain and the effector caspases-3 and -7 via its BIR2 domain. A natural inhibitor of XIAP is SMAC/Diablo which is released from mitochondria in apoptotic cells and displaces bound caspases from the BIR2/BIR3 domains of XIAP thereby reactivating cell death execution. The central apoptosis-inhibitory function of XIAP and its overexpression in many different types of advanced cancers have led to significant efforts to identify therapeutics that neutralize its anti-apoptotic effect. Most of these drugs are chemical derivatives of the N-terminal part of SMAC/Diablo. These “SMAC Mimetics” either specifically induce apoptosis in cancer cells or act as drug-sensitizers. Several “SMAC Mimetics” are currently tested by the pharmaceutical industry in Phase I and Phase II trials. In this review we will discuss recent advances in understanding the function of IAPs in normal and malignant cells and focus on approaches to specifically neutralize XIAP in cancer cells.